Management of MDR-TB in HIV co-infected patients in Eastern Europe: Results from the TB:HIV study. Issue 1 (January 2018) - Efsen, A.M.W.; Schultze, A.; Miller, R.F.; Panteleev, A.; Skrahin, A.; Podlekareva, D.N.; Miro, J.M.; Girardi, E.; Furrer, H.; Losso, M.H.; Toibaro, J.; Caylà, J.A.; et al.
Highlights: Management of TB/HIV co-infected patients in Eastern Europe (EE) is suboptimal. TB/HIV co-infected patients diagnosed with MDR-TB received inferior TB treatment with limited numbers of active drugs. Access to rapid diagnostics for TB is urgently needed. Performance of extended DST for all patients diagnosed with MDR-TB is required. Integration of TB and HIV clinics can potentially ensure better management of patients in EE. Summary: Objectives: Mortality among HIV patients with tuberculosis (TB) remains high in Eastern Europe (EE), but details of TB and HIV management remain scarce. Methods: In this prospective study, we describe the TB treatment regimens of patients with multi-drug resistant (MDR) TB and use of antiretroviral therapy (ART). Results: A total of 105 HIV-positive patients had MDR-TB (including 33 with extensive drug resistance) and 130 pan-susceptible TB. Adequate initial TB treatment was provided for 8% of patients with MDR-TB compared with 80% of those with pan-susceptible TB. By twelve months, an estimated 57.3% (95%CI 41.5–74.1) of MDR-TB patients had started adequate treatment. While 67% received ART, HIV-RNA suppression was demonstrated in only 23%. Conclusions: Our results show that internationally recommended MDR-TB treatment regimens were infrequently used and that ART use and viral suppression was well below the target of 90%, reflecting the challenging patient population and the environment in which health care is provided. Urgent improvement of management of patients with TB/HIV in EE, in particular for those with MDR-TB, is needed and includes widespread access to rapid TB diagnostics, better access to and use of second-line TB drugs, timely ART initiation with viral load monitoring, and integration of TB/HIV care.